Clinical Profile and Treatment Outcome in MOGAD: A Single-Center Case-Series Study in Guiyang, China - Lei, Xiaoyang; Guo, Shipeng; Cui, Shengnan; Pu, Yin; Zhang, Anni; He, Dian (Frontiers in Neurology, 2022)
Background: The clinical spectrum of myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is expanding over time. However, the long-term management and prognosis of this disorder are still controversial. This study aims to report the clinical profiles and treatment outcomes of MOGAD. Methods: This was a single-center case-series study, clinical and paraclinical data, treatment outcomes of MOGAD patients were analyzed. Results: A total of 27 patients were identified, 19 (70%) patients were female, and the median age at disease onset was 40 years (range 20-67). A total of 47 episodes were observed, optic neuritis (53%) was the most frequent presentation and 60% of them were unilateral. Other presentations included rhombencephalitis (RE) (17%), limbic encephalitis (9%), simultaneous optic neuritis and myelitis (9%), acute disseminated encephalomyelitis (ADEM)-like presentation (6%), myelitis (4%), and ADEM (2%). One patient presenting with RE also met the diagnostic criteria of area postrema syndrome . Another RE patient presented with imaging characteristics of chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS). A total of 29 lumbar punctures were recorded, an elevated protein level was found in 34% of the samples, pleocytosis was found in 14% of the samples, and positive intrathecal oligoclonal bands were found in 19% of the patients. One patient was found to have anti-N-methyl-D-aspartate receptor antibody both in his serum and cerebrospinal fluid. Intravenous methylprednisolone (IVMP) was administrated for 85% of the attacks while both IVMP and intravenous immunoglobulin were for 6% of the attacks. Nine patients received maintenance therapy. Among them, six patients were treated with mycophenolate mofetil, three patients were treated with prednisone, rituximab and teriflunomide respectively. The median follow-up period was 20 months (range 6-127). Twelve (44%) patients experienced a relapsing course, and the median time to the first relapse was 9.5 months (range 2-120). The median Expanded Disability Status Scale score at nadir was 3.5 (range2-8), at last follow-up was 0 (range 0-3). Conclusion: The clinical spectrum of MOGAD is heterogenous, APS and CLIPPERS-form can occur. The long-term outcome of MOGAD seems benign. Further studies are warranted to determine the risk factors of relapse and identify the optimal steroid-sparing agents.